FACTORS AFFECTING RURAL INCOME IN PAKISTAN: A MICRO STUDY - M. Zahir Faridi; Mah Rukh Shabbir; Ukasha Kirn; Khawaja Asif Mehmood; Zahida Niaz (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The basic purpose of the study is to examine the determinants of rural income in Pakistan. Generally, it was considered that cultivation of crops and livestock ranching are the main source of rural income. But there are many other factors that affect the rural income. In order to examine determinants of rural income, we have used Log-Linear Model for the analysis. Estimated results are demonstrating the mixture of positive and negative relationship with our targeted variable. Rural income presents negative relationshipwith family setup, major diseases and marital status while age, education, gender, employment status, land holding, no of livestock, availability of roadsisdirectly linked with the rural income. It is suggested that Government should brought changes in livestock-based industries.